External doses from plated-out decay products in radon-rich enclosed spaces. Issue 1 (1st February 2022) - Mostacci, D.; Moroder, E.; Cucchi, G.
Abstract : In caves in the Alps, where Radon can reach concentrations of tens of or hundreds of kBq/m 3, the deposition of decay products on the skin of personnel spending even short times inside may pose a radiological risk. The radiation protection expert (RPE) is confronted with evaluating on the spot, and quickly, this hazard, to take appropriate measures as needed. In the present work, estimates are proposed to assess this problem, estimates that can be used by the RPE for the needed screening to categorize the risk presented by these environments.